2015
DOI: 10.1002/ejoc.201500630
|View full text |Cite
|
Sign up to set email alerts
|

Nickel‐Catalyzed Decarbonylative Cou­pling of Aryl Esters and Arylboronic Acids

Abstract: A variety of functionalized biaryls can be accessed by coupling aryl and heteroaryl esters with boronic acids in Suzuki–Miyaura‐type decarbonylative cross‐coupling catalyzed by an affordable catalyst system composed of Ni(cod)2 and PCy3. The methodology is tolerant of a variety of functional groups and presents an attractive alternative to the use of palladium catalysis currently used in industry to acquire such bis(hetero)aryls, but also reveals challenges associated with nickel catalysis of esters in cross‐c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 86 publications
(24 citation statements)
references
References 84 publications
(27 reference statements)
0
24
0
Order By: Relevance
“…Additional ligands resulted in inferior results, which may indicate saturation of the coordination sphere of the Ni catalyst. Previous studies suggested that a single phosphane ligand might be required to facilitate metal insertion into a C−X bond (X=N, O) . π‐Deficient ligands had a negative impact on the reaction (see the Supporting Information) .…”
Section: Figurementioning
confidence: 99%
“…Additional ligands resulted in inferior results, which may indicate saturation of the coordination sphere of the Ni catalyst. Previous studies suggested that a single phosphane ligand might be required to facilitate metal insertion into a C−X bond (X=N, O) . π‐Deficient ligands had a negative impact on the reaction (see the Supporting Information) .…”
Section: Figurementioning
confidence: 99%
“…To furthere xplore the electron distribution in the ground state of these p-systems, we applied charge decomposition (CDA), [104,105] natural bond orbital (NBO), [106] andq uantum Figure 1. Normalized Ni K-edgePFY XANES edge spectraf or Ni(dtbpe)Cl 2 (12), [Ni(dtbpe)] 2 (benzene) (7), Ni(dtbpe)(ethylene)( 4), Ni(dtbpe)CF 3 COOEt (1), and Ni(dtbpe)CF 3 COSEt (2). The pre-edge regionf or each of the spectra is shown in the inset with assignmentsf or the observed features.…”
Section: Computational Studies (Dft)mentioning
confidence: 99%
“…We have recently become interested in exploring the fundamental organometallic chemistry of earth-abundant, first-row transition metals. For example, we are exploring the organometallicc hemistry of nickel, [10][11][12][13][14] which has undergone ar enaissance in recent years. [15][16][17][18][19][20][21] Our focus has been the structure and reactivityo fn ickel p-complexes, which have been reported in aw ide range of catalytic processes, including the coupling of CO 2 and ethylene, [5,[22][23][24][25][26][27][28][29][30][31][32] intermolecular Tischenkoc oupling, [33][34][35] benzoxasilole synthesis, [36,37] the aldol reaction, [38] allylic alkylation, [39] allylic amination, [40] allylic amidation, [41] epoxide functionalization, [42] and Suzuki-Miyaura coupling.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar decarbonylative Suzuki‐Miyaura reaction was reported by Love and co‐workers in 2015 (Scheme ), in which esters containing heterocycles could be accommodated with various arylboronic acids in unsatisfactory yields. On the other hand, the mixture of non‐decarbonylative products, ketones, and decarbonylative products, biaryls, was afforded using aryl esters.…”
Section: Decarbonylative Arylation Reactionmentioning
confidence: 99%